Communicative Competence as a Basic Element in the Development of the Pedagogical Culture of the Future Educator - Otajonov Jamshid Mashrabjonovich; Dadajonova Zarnigor Foziljon qizi (Zien Journals, 2022)
the article presents ideas on the formation of the communicative ability of a teacher of a preschool educational organization. It has been revealed to scientists who have conducted research in this regard and their research.
Keywords: competence; professional competence; communicative competence